Strategi Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran Melalui Supervisi Akademik - Amelia Sarah Fatihah; Diningrum Citraningsih; Fatimah Arisika Putri (Kartika: Jurnal Studi Keislaman, 2026)
The principal's strategy plays an important role in improving the quality of learning, one of which is through academic supervision. Academic supervision serves as a means of enhancing teachers’ professional competence, thereby contributing to the quality of the learning process. This study aims to describe the principal's strategy in improving learning quality through academic supervision at MI Muhammadiyah 27 Geger and to identify the supporting and inhibiting factors in its implementation. The research employed a qualitative approach with data collected through observation, interviews, and documentation. Data were analyzed through the stages of data collection, data reduction, data display, and conclusion drawing, while data validity was ensured through technical triangulation. The findings reveal that the academic supervision strategy was implemented through four stages: supervision of learning planning, supervision of learning implementation, supervision of teacher development and performance assessment, and evaluation with follow-up actions. The implementation of these strategies was proven to enhance teachers’ motivation, teaching readiness, and professional competence, which in turn contributed to improving the quality of learning and students’ learning outcomes